A new bio-oxidation method for removing iron deposits from waterlogged wood of Nanhai I shipwreck, Guangdong, China - Yishu Wang; Zijun Zhao; Jianqun Lin; Qinglin Ma; Linxu Chen (Engineering Microbiology, 2024)
The widespread presence of iron and sulfur compounds such as pyrite in marine waterlogged archeological wood (WAW) can cause irreversible damage to the safety of its preservation. This issue has been a longstanding concern for cultural heritage conservation communities. In this study, we examined the distribution and phase composition of Fe and sulfur compounds in wood samples obtained from the Nanhai I shipwreck using ESEM-EDS, micro-Raman spectroscopy, and an X-ray diffractometer. The removal of iron from WAW samples of the Nanhai I shipwreck using Acidithiobacillus ferrooxidans (A. ferrooxidans) was evaluated using conductivity and ICP-AES analysis. The results showed that A. ferrooxidans effectively improved the removal of iron from WAW. The degradation of fresh healthy wood during treatment was also analyzed using infrared spectroscopy, and the results showed that the treatment had little effect on the samples over a short period. This study demonstrates, for the first time, the feasibility of iron extraction from marine WAW by A.ferrooxidans. This was also the first attempt in China to apply biological oxidation to the removal of iron from marine archeological materials.